2015
DOI: 10.1016/j.cbpa.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic approaches to protein phosphorylation

Abstract: Reversible protein phosphorylation is critically important in biology and medicine. Hundreds of thousands of sites of protein phosphorylation have been discovered but our understanding of the functions of the vast majority of these post-translational modifications is lacking. This review describes several chemical and biochemical methods that are under development and in current use to install phospho-amino acids and their mimics site-specifically into proteins. The relative merits of total chemical synthesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 67 publications
(68 reference statements)
1
100
0
Order By: Relevance
“…To gain further insight into the role of pTyr369, we used protein semisynthesis (Muir et al, 1998) in the context of 2,3-linkerL-WW3-WW4-HECT WWP2 (aa 356-870) to site-specifically install a pTyr residue at this position. In this method, a synthetic peptide (aa 356-373) containing pTyr369 and a C-terminal thioester (Blanco-Canosa and Dawson, 2008) is chemoselectively ligated to an N-Cys containing WWP2 recombinant fragment (Figure 4B and 4C) (Chen and Cole, 2015). This ligation strategy introduces a Cys in place of Ser374, which was shown to be non-perturbing for WWP2 catalysis (Figure S5B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain further insight into the role of pTyr369, we used protein semisynthesis (Muir et al, 1998) in the context of 2,3-linkerL-WW3-WW4-HECT WWP2 (aa 356-870) to site-specifically install a pTyr residue at this position. In this method, a synthetic peptide (aa 356-373) containing pTyr369 and a C-terminal thioester (Blanco-Canosa and Dawson, 2008) is chemoselectively ligated to an N-Cys containing WWP2 recombinant fragment (Figure 4B and 4C) (Chen and Cole, 2015). This ligation strategy introduces a Cys in place of Ser374, which was shown to be non-perturbing for WWP2 catalysis (Figure S5B).…”
Section: Resultsmentioning
confidence: 99%
“…Although Glu is typically of limited reliability as a mimic of pTyr (Chen and Cole, 2015), analysis of the autoinhibited WWP2 crystal structure suggested that Glu replacement of Tyr369 or Tyr392 could be similarly disruptive as tyrosine phosphorylation to the linker-HECT interactions. Replacement of either Tyr369 or Tyr392 with Glu as the single or double mutants in recombinant full-length WWP2 stimulated its autoubiquitination activity, although these Y/E mutants were still less active than full 2,3-linker deletion (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
“…This study also illustrates the power of expressed protein ligation in elucidating how a complex series of PTMs can alter the structure of a protein (24). Because mass spectrometry has identified hundreds of thousands of PTMs in proteins, it has become daunting to cope with illuminating the structural and functional effects of these PTMs at an individual protein level.…”
Section: Discussionmentioning
confidence: 99%
“…[1] This also applies to mechanistic investigations of "phosphoregulation", in which access to site-specifically phosphorylated proteins is required. [2] Recombinant methods afford folded phosphoproteins. [3] However,t he limited availability of suitable protein kinases restricts the global analysis of alternative protein phosphoforms.F or example,t he SH3 domain of the Abl protein, an onreceptor tyrosine kinase critically involved in chronic myelogenous leukemia (CML), [4,5] is found phosphorylated at each of its three tyrosine residues (Y 7 ,Y 30 ,Y 52 ).…”
mentioning
confidence: 99%